(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The Present study is an attempt to articulate, explain and examine the concepts of state in politics used by an ongoing tradition of enquiry of State System and Moral Values of Indian Political Philosophy the founder and political guru Raja guru or Royal priest of Vijayanagar dynasty and PIOS guru of Hakka and Bukka Of Indian political philosophy and the academia of Indian political science. A similar work with regard to the realization of the historical evaluation of the western political thought from Socrates and Aristotle to Machiavelli, Hobbes and Rousseau’s and to marks and Lenin by Dunning, Catlin, Hearn haw and others Hence the academia research scholars of philosophy and political thought have a much needed awareness and research of Indian political philosophers.